2015
DOI: 10.18632/oncotarget.3746
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal tumor spread in serous ovarian cancer-epithelial mesenchymal status and outcome

Abstract: In this study we aimed to analyze the biological mechanisms underlying apparently different modes of peritoneal tumor spread in serous ovarian cancer: miliary (widespread, millet-like lesions) versus non-miliary (bigger, exophytically growing implants). Tumor tissues and ascites from 23 chemotherapy naive patients were analyzed by RNA-sequencing and flow cytometry. On the basis of differential gene expression between miliary and non-miliary, gene signatures were developed. A calculated tumor spread factor reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 39 publications
10
81
1
Order By: Relevance
“…Specifically, 10/22 genes were differently expressed, namely BAG1, BIRC5, CCNB1, CLDN4 and 6, MMP9 and 11, MUC1, MYBL2, and SERPINB3. This finding of a gene signature for ascites-producing PC is consistent with previous data analyzing differences in gene expression between PC with miliary and non-miliary peritoneal spread [33]. In this study, Auer et al analyzed tumor tissues and ascites from 23 chemotherapy-naive patients by RNA-sequencing and flow cytometry.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, 10/22 genes were differently expressed, namely BAG1, BIRC5, CCNB1, CLDN4 and 6, MMP9 and 11, MUC1, MYBL2, and SERPINB3. This finding of a gene signature for ascites-producing PC is consistent with previous data analyzing differences in gene expression between PC with miliary and non-miliary peritoneal spread [33]. In this study, Auer et al analyzed tumor tissues and ascites from 23 chemotherapy-naive patients by RNA-sequencing and flow cytometry.…”
Section: Discussionsupporting
confidence: 91%
“…2.54 for miliary (Table 2C), with the HR obtained in the training cohort with the 272 gene spread predictor [11] (HR = 1.74, CI 95 1.06–2.86, Table 2A). Again, the validation HR was within the CI 95 of the HR in the training cohort, indicating a successful validation.…”
Section: Resultsmentioning
confidence: 96%
“…It did not correlate with any of the clinicopathological parameters (age, FIGO stage, grade, and residual tumor). As we have already reported an independent negative prognostic impact on OS of the miliary spread type (predicted with a 272 gene spread predictor ) in our previous study [11], we applied this multiple Cox regression model to the validation cohort (Table 2A) replacing the 272 gene spread predictor with the 13 sRNA spread predictor . The risk for each patient from the validation cohort was calculated using the Cox regression model from the training cohort with the 13 sRNA spread predictor value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that opposing levels of E-Cadherin and vimentin occur in cells that have undergone EMT [60, 61]. Therefore, this new cell line may be an interesting model to study EOC processes related to peritoneal metastasis and invasion, because there is evidence that EMT transition might be involved in this tumor spread [62]. All the other five cell lines showed patterns of epithelial origin as suggested by the presence of cytokeratins and/or E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%